ANALISA PENDAPATAN USAHA TERNAK AYAM POTONG (Studi Kasus Peternakan Milik Dani L. Di Kecamatan Karang Ploso) - Sunardi Sunardi; Nonok Supartini (BUANA SAINS, 2010)
The objectives of the research were (1) to analyze the level of profit of broiler cattle business, and (2) to find out the fit of broiler cattle business of Bapak Dani’s Farm in Bocek Village, Karangploso Sub District, Malang Regency. The research was conducted at Bapak Dani’s Farm in Bocek Village, Karangploso Sub District, Malang Regency on October 10th, 2007 until November 10th, 2007. The material used in this research was one of farm in Bocek Village, Karangploso Sub District, Malang Regency. The method used in determining the respondent was by using purposive sampling. The data analyzed were primary data taken directly from the farm, and secondary data taken from related institution. Data analysis used descriptive method covering income analysis; Break Even Point (BEP), and cattle business fit analysis using R/C ratio approach. The conclusions of the research were: (1) the cost needed in broiler maintenance business in research location was IDR 13,120/broiler.; the revenue got was IDR 16,409/broiler and the income got was IDR 3,289/broiler; (2) the broiler maintenance business researched in scale of ownership of 1,500 broilers was proper to be developed since R/C ratio showed 1.25. This showed that the farmer got profit of 25% from his business. It was suggested that: (1) the farmer kept on maintaining the business pattern in order to get proper profit; (2) the government should give information program about farming pattern in a good way and give also medicines to help farmers in order to increase their production